Actual Use of Specialized Accounting Statements. - Copeland, Ronald M.; Moore, Michael L. (The Accounting Review, 1968)
Abstract This article reports on a study of the extent to which certain specialized accounting statements presented in accounting textbooks are actually used in practice. To determine the extent of use and form in which these statements are prepared, fifty bankrupt or liquidated companies in the six-year period were selected. These companies were contacted by mailed questionnaire. Each questionnaire was accompanied by a typical textbook model of the appropriate specialized accounting statement. In addition to the questionnaire information, examples of statements and numerous comments were also received. From these sample statements and comments it was clear that when statements are prepared in cases of bankruptcy or liquidation, they generally take on the configuration of the conventional balance sheet. It was concluded in the study that statements prepared for bankruptcy, liquidation, loan or credit purposes are rarely found in practice in the same form as is conventionally depicted in accounting textbooks.